An Analysis of HVDC Implementation Strategies for Enhancing Power Transmission in Azerbaijan - Aliyeva, Sabina (ADA University, 2023)
This research endeavors to evaluate and compare High Voltage Direct Current (HVDC) implementation strategies for augmenting power transmission within Azerbaijan. The study delves into the efficacy of HVDC technology by conducting a comparative analysis between traditional Alternating Current (AC) transmission and innovative HVDC lines. Utilizing 'Dig Silent Power Factor' software, the research investigates the transmission of 500MW of electrical energy across a 500km stretch, addressing voltage disparities between border systems. The comparative analysis reveals compelling insights into the efficiency of HVDC systems. The AC model, employing multiple transmission lines and autotransformers, displayed notable losses, whereas the HVDC model exhibited remarkably minimized losses, highlighting its superior efficiency in transmitting power over extensive distances. [1] Moreover, the study contextualizes Azerbaijan's commitment to sustainability and emission reduction within the global framework, recognizing the pivotal role of innovative energy infrastructure. It emphasizes the potential of HVDC technology in unlocking the nation's renewable energy resources, reducing reliance on fossil fuels, and fostering a cleaner, more sustainable energy grid. This research underscores the significance of HVDC implementation strategies in Azerbaijan's quest for sustainable energy transmission. It advocates for the adoption of HVDC technology as a transformative step toward a greener future, positioning Azerbaijan as a progressive hub in energy innovation and global sustainability efforts. This study contributes substantively to Azerbaijan's ambitious energy plans, shedding light on the pragmatic advantages of HVDC systems in optimizing power transmission efficiency. As Azerbaijan navigates its evolution from a traditional energy powerhouse to a burgeoning green energy exporter, this research underscores the pivotal role of innovative transmission technologies in realizing sustainable energy aspirations while consolidating Azerbaijan's position as a reliable global energy player
Keywords: Green technology -- Government policy; Energy conservation -- Environmental aspects; Energy sustainability; High voltages; IT and Engineering